2014
DOI: 10.4314/jab.v78i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selected essential oil plants on bacterial wilt disease development in potatoes

Abstract: Objective: Bacterial wilt disease caused by Ralstonia solanacearum is a major constrain to production of potatoes (Solanum tuberosum). Control of bacterial wilt is very difficult as there are no effective curative chemicals. This study was aimed at investigating the potential roles of essential oil plants in control of the disease. Methodology and Result: The plants used included: Lippie javanica (Sage brush), Ocimum suave (Cambodia) and Tarchonanthus camphorates (Camphor brush).Experiments were conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
2
8
0
Order By: Relevance
“…The varied antibacterial activity between the plant extracts can be attributed to diversity and or difference in concentrations of secondary metabolites in each plat extract ( Yihune and Yemata 2019 ). These in-vitro results were in accordance with those of Oboo et al, 2014 , Biswal, 2015 who reported antibacterial activity of these plant extracts against R. pseudosolanacearum sp. nov. in-vitro.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The varied antibacterial activity between the plant extracts can be attributed to diversity and or difference in concentrations of secondary metabolites in each plat extract ( Yihune and Yemata 2019 ). These in-vitro results were in accordance with those of Oboo et al, 2014 , Biswal, 2015 who reported antibacterial activity of these plant extracts against R. pseudosolanacearum sp. nov. in-vitro.…”
Section: Discussionsupporting
confidence: 92%
“…The phytobiocidal effect of various plant extracts against R. pseudosolanacearum sp. nov. has been demonstrated by several researchers both in-vitro and in-vivo ( Hassan et al, 2009 , Oboo et al, 2014 , Din et al, 2016 , Mutimawurugo et al, 2020 , Wamani, 2020 ). However, the phytochemical composition of these bioactive compounds varies from one plant to another and their effectiveness is also affected by variation in agro-climatic conditions coupled with varied abiotic factors during plant growth ( Liu et al, 2016a , Liu et al, 2016b , Kumar et al, 2017 , Gololo, 2018 ).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The disease rating decreased from 4.2 in the control to 1.6 and 2.2 in plants treated with TEO and VEO, respectively. These results had the confirmation of Oboo et al, (2014) who indicated that EOs decreased the disease incidence of bacterial wilt of potato. The decrease of disease rating may due to the inhibitory effect of the two EOs against the test bacterial pathogen and the increase of systemic induced resistance of potato plant.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, the EOs are considered a new horizon to fight the bacterial antibiotic resistance (Yap et al, 2014). Oboo et al (2014) revealed that the EOs of Tarchonanthus camphorates (Camphor brush), Ocimum suave (Cambodia) and Lippie javanica (Sage brush) significantly reduced the bacterial wilt disease of potato. Li and Yu (2015) reported that the EO obtained from the leaves of Macleaya cordata R. Br.…”
Section: Introductionmentioning
confidence: 99%